Eradication of Plastic Carry Bags: The Shop Owners' Perception - Valarmathy, P. S. (Indian Journal of Marketing, 2015)
Polythene bags, popularly referred to as plastic carry bags, are one of the most hazardous substances in the world, causing a lot of damage to the earth and its sustainability. Since the main source of supply of the plastic carry bags to the public are the shop owners, that is, super markets, vegetable&fruit vendors, and bakery and grocery stores, an empirical study was undertaken to assess the awareness of the shop owners about the hazards of plastic carry bags and their perceptions on how to eradicate them. Statistical tools like chi square test, weighted arithmetic mean, and K means cluster analysis were used to analyze the data collected from 400 shop owners belonging to various types of businesses. Three clusters of shop owners were identified - namely Defaulters, Ignorant Defaulters, and Partial Compliers. Bakery and grocery stores were found to be the major defaulters. The study found that strict implementation of the Plastic Waste Management and Handling Rules is the need of the hour.